PENGARUH PEMBERIAN AROMA TERAPI LEMON ELEKTRIK TERHADAP MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER I - Detty Afriyanti; Nurul Huda Rahendza (Maternal Child Health Care, 2020)
Nausea and vomiting in pregnancy are the most common conditions of pregnancy women, it happens between 5 to 8 pregnancy weeks . The aim of this study was to determine The Effectiveness of Aroma Electric Lemon Therapy toward Nausea and Vomiting of the First Trimester Pregnant Women in BPM "R" Bukittinggi 2019. This study used experiment with one-time pretest posttest. It was conducted on october 2019. The populations and samples were 15 respondents. The data were collected through observation by using observation sheet and it was analyzed by frequency distribution and T-test statistical tests with Confidence Interval 95% or α 0,05. The results of the statistical test showed that the average value before was 5.27 and after was 3.27. The average difference before and after given lemon electric aromatherapy was 2.000 with p = 0.005 It means that, there is an effect of electric lemon aromatherapy. Based on the results of the study, it can be concluded that electric lemon aromatherapy was also effective in reducing nausea and vomiting in pregnant women in the first trimester. Based on this, it is expected that pregnant women could independently apply this therapy.